Antimicrobial peptides expressed in the fat body of Spodoptera frugiperda (Lepidoptera: Noctuidae) in response to the microbial challenge (Research, Society and Development, 2022)
Spodoptera frugiperda (Lepidoptera: Noctuidae) is the key pest in maize crops and has a major impact on world agriculture. Several studies on the biological control of this species have been carried out, and these demonstrate resistance to biological control and pesticides. However, the humoral immune system of S. frugiperda is not yet completely known in relation to the innate immune response to biological control agents. The aim of this study was to evaluate the expression of Gloverin, Sf-gallerimycin, and Attacin genes in the fat body of larvae at the 6th instar of development. Our work confirmed the expression of Sf-gallerimycin in response to the bacterial challenge, 24 h post-inoculation, and revealed the expression of Gloverin and Attacin for the first time for both bacterial challenge and entomopathogenic fungus Beauveria bassiana challenge. Gloverin and Attacin genes were upregulated under the conditions analyzed. In addition, we revealed the presence of two probable antimicrobial peptides in the hemolymph, induced 24 h post challenge with the microorganisms. The 4.7 kDa band b is probably a defensin-like peptide, and the 6.1 kDa band a is a peptide not yet reported in S. frugiperda.